The worlds of John Wick : the year's work at the Continental Hotel - Watt, Caitlin G.; Watt, Stephen (Year's work (Bloomington, Ind.), 2022)
-- Stephen Watt is located in Bloomington, IN --Caitlin Watt is located in Clemson, SC -- The editors and contributors to this volume are from a wide range of disciplines to address all aspects of John Wick worldbuilding and are best for this work because they are responsible for the research at ""The World(s) of John Wick"" conference in November 2019. -- Whether you consider the John Wick film franchise to be full of instant cult classics or surprise hits, the movies are no doubt a nostalgic throwback to revenge-thrillers popularized in the 1970s while featuring the action impulses of Kung F